Development Strategy in Increasing Tourist Visits in Cemagi Tourist Village - Ganang Aditiyo Prakoso; Marmaiyatno; Baskoro Harwindito (International Journal of Travel, Hospitality and Events, 2025)
Purpose: Determine the internal and external factors that support and hinder development in Cemagi Tourism Village and Determine the best alternative strategy analysis for Cemagi Tourism Village. Research methods: This research uses a qualitative approach. The sampling technique used in this research is purposive sampling. The data analysis used in this research is SWOT. Results and discussion:The results of this research are the strategies that can be implemented in developing the Cemagi Tourism Village to increase the number of tourist visits, including: (1) SO Strategy: Creating Cemagi trek tour packages, agrotourism and cultural tourism, and making promotions about Cemagi's tourism; (2) WO Strategy to improve infrastructure or create infrastructure that supports tourism in Cemagi; (3) ST Strategy: Creating a different program from other tourist villages; (4) WT Strategy Create a village security program. Implication: Based on the results and discussion of this research, the researcher recommends implementing the strategies that she has created, such as improving the existing infrastructure in the Cemagi Tourism Village. The tourist village should be more aggressive in its promotion, especially on social media. It would be better to collaborate with travel agents when selling tour packages. Collaborate with the government to create an event that can attract tourists to the Cemagi Tourism Village.